A new pyrrole based small molecule from Tinospora cordifolia induces apoptosis in MDA-MB-231 breast cancer cells via ROS mediated mitochondrial damage and restoration of p53 activity. (1st February 2019) - Rashmi, K.C.; Harsha Raj, M.; Paul, Manoj; Girish, Kesturu S.; Salimath, Bharathi P.; Aparna, H.S.
Abstract: Approximately 15% of globally diagnosed breast cancers are designated as triple negative breast cancer (TNBC). In this study, we investigated the effect of the natural compound, Bis(2- ethyl hexyl) 1H-pyrrole-3, 4-dicarboxylate (TCCP), purified from Tinospora cordifolia on MDA-MB-231, a TNBC cell line. The pro-apoptotic nature of TCCP on MDA-MB-231 was determined by assessing various apoptotic markers. ROS generation, intracellular calcium, mitochondrial membrane potential (ΔΨ m ), MPTP, cardiolipin peroxidation and caspase activity were determined fluorometrically. BAX, BCL-2, cytochrome c, caspases, and p53 protein expressions were determined by immunoblotting. Further, the effect of TCCP on DNA and cell death was determined by DNA fragmentation assay, annexin-V staining, and cell cycle analysis. TCCP treatment caused endogenous ROS generation, increase in intracellular calcium and phosphorylation of p53 in a concentration-dependent manner, which was reverted upon pre-treatment with pifithrin-μ. This led to the downstream altered expression of Bcl-2 and Bax proteins, mitochondrial membrane depolarization, MPTP, and cardiolipin peroxidation. TCCP induced cytochrome c release into the cytosol, caspase activation, ultimately resulting in DNA fragmentation. Further, induction of apoptosis and morphological alterations were evident from the phosphatidylserine externalization and increase in sub G1 population. The in vivo Ehrlich ascites tumor (EAT) mouse study revealed the effectiveness of TCCP in reducing the tumor burden and resulted in a ~2 fold increase in mice survival with minimal hepato-renal toxicity. Overall, TCCP was shown to be efficient in inducing ROS and mitochondrial-mediated apoptosis by restoring p53 activity in MDA-MB-231 cells and also induced EAT cell death in vivo thereby inhibiting tumor proliferation. Graphical abstract: Highlights: TCCP inhibits proliferation of breast cancer cell line MDA-MB-231. TCCP triggers ROS accumulation, ER stress, alterations in Δψm, Cyt c release. TCCP activates apoptogenic proteins and induces caspases. Inhibition of p53 by pifithrin-μ reversed the effects of TCCP treatment. In vivo, TCCP effectively reduced tumor burden in Ehrlich ascites tumor model.